The physical health of Māori with bipolar disorder. (November 2020) - Cunningham, Ruth; Stanley, James; Haitana, Tracy; Pitama, Suzanne; Crowe, Marie; Mulder, Roger; Porter, Richard; Lacey, Cameron
Aims: There is very little empirical evidence about the relationship between severe mental illness and the physical health of Indigenous peoples. This paper aims to compare the physical health of Māori and non-Māori with a diagnosis of bipolar disorder in contact with NZ mental health services. Methods: A cohort of Māori and non-Māori with a current bipolar disorder diagnosis at 1 January 2010 were identified from routine mental health services data and followed up for non-psychiatric hospital admissions and deaths over the subsequent 5 years. Results: Māori with bipolar disorder had a higher level of morbidity and a higher risk of death from natural causes compared to non-Māori with the same diagnosis, indicating higher levels of physical health need. The rate of medical and surgical hospitalisation was not higher among Māori compared to non-Māori (as might be expected given increased health needs) which suggests under-treatment of physical health conditions in this group may be a factor in the observed higher risk of mortality from natural causes for Māori. Conclusion: This study provides the first indication that systemic factors which cause health inequities between Māori and non-Māori are compounded for Māori living with severe mental illness. Further exploration of other diagnostic groups and subgroups is needed to understand the best approach to reducing these inequalities.